Radial, renal and craniofacial anomalies: Baller-Gerold syndrome - Jyotsna Murthy; Ramesh Babu; Padmasani Venkat Ramanan (Indian Journal of Plastic Surgery)
The Baller-Gerold syndrome is a rare syndrome with very few cases published in literature. Craniosynostosis and radial aplasia are striking features, easy to diagnose. However, there are many differential diagnoses. Often, the question raised is whether the Baller-Gerald syndrome is a distinct entity. We report a patient with findings of craniosynostosis and radial aplasia consistent with the diagnosis of the Baller-Gerold syndrome. Genotypic heterogeneity could possibly underlie the phenotypic variability exhibited by these cases.